2010
DOI: 10.1007/s11627-010-9287-6
|View full text |Cite
|
Sign up to set email alerts
|

An efficient protocol for micropropagation of Melaleuca alternifolia Cheel

Abstract: Melaleuca alternifolia is cultivated for the production of an essential oil useful in the cosmetic and pharmaceutical industries. Despite the economic importance of this species, there is little knowledge about its in vitro propagation. The aim of this study was to establish an efficient protocol for micropropagation of M. alternifolia. With the goal of in vitro multiplication by axillary shoot proliferation, both solid and liquid MS and WPM media were tested with supplementation with BA at 0, 0.55, 1.11, 2.22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
5
9
0
Order By: Relevance
“…We found that the presence of auxins was unnecessary for in vitro rooting of 'Shidareguwa' mulberry, which is similar to results for M. acidosa (Enomoto, 1987) and other species (Morimoto et al, 1994;Oliveira et al, 2010). The relationship between auxins, carbohydrates, and rooting is complex and remains unclear.…”
Section: Rooting Acclimation and Transfer Of Plantlets To Fieldsupporting
confidence: 80%
“…We found that the presence of auxins was unnecessary for in vitro rooting of 'Shidareguwa' mulberry, which is similar to results for M. acidosa (Enomoto, 1987) and other species (Morimoto et al, 1994;Oliveira et al, 2010). The relationship between auxins, carbohydrates, and rooting is complex and remains unclear.…”
Section: Rooting Acclimation and Transfer Of Plantlets To Fieldsupporting
confidence: 80%
“…Anatomical characteristics change in hyperhydric shoots and several types of abnormal structures can be recognized (Ziv 1991). Several factors can induce the hyperhydricity in explants, such as high BAP levels (Oliveira et al 2010), cultivar (Carvalho et al 2013), and agar concentration (Abdoli et al 2007) but the most common cause of the hyperhydricity occurrence is the culture in liquid medium (Scheidt et al 2011;Silva et al 2012). Some species are so sensitive to this physiological change that even when cultivated in solid medium with a low BAP level, hyperhydricity occurs, as it is the case for L. angustifolia.…”
Section: Lavandula Angustifolia Mill (Syn L Officinalismentioning
confidence: 99%
“…The roots induced in vitro may be important reserves of carbohydrate, as verified in the bromeliad Aechmea blanchetiana (Baker) LB Smith (Chu et al 2010). However, the roots produced during the in vitro culture stage may have been functionally limited, with impaired water and mineral absorption, even after transfer to ex vitro conditions (Oliveira et al 2010). Thus, the formation of new roots during the ex vitro stages is important (Hazarika 2006) and can be affected by abiotic factors, such as the spectral quality and quantity of light, which are known to stimulate root growth and overall irradiance levels and to affect the accumulation of photoassimilates (Huang et al 2011a).…”
Section: Discussionmentioning
confidence: 99%